Identification of Suitable Perennial Host for Sandal in Nursery and Field - Anandalakshmi, R.; Karthikeyan, A.; Suresh Kumar, K.; Rajesh, C.; Geetha, S.; Murugan, E.; Ananthakumar, M. (Indian Forester, 2023)
Santalum album is a hemi-parasite tree species native to India. Its fragrant heartwood and oil are of high economic value across the globe. Restoration, domestication and cultivation of sandal is gaining importance in the recent times due to its dwindling populations. Raising sandal nursery and field establishment require scientific inputs to promote sandal rejuvenation especially to establish haustoria (nutritive organ). An experiment was conducted in order to identify suitable perennial host for sandal that can serve both as primary and secondary host. Among the ten different hosts tested, three species namely Pithecellobium dulce, Duranta repens and Casuarina junghuhniana were found to improve the growth of sandal in the nursery. These species recorded haustorial formation in the roots in the order of P. dulce (62.5%) >C. junghuhniana (45%) >D. repens (32.5%). Thus the shortlisted three suitable hosts were raised along with sandal in polybags for six months and field planted along with sandal. Sandal growth parameters such as height, collar diameter and crown circumference were recorded at intervals of 3, 6, 9, 12, 15, 21 and 29 months. Results showed that P. dulce is the most appropriate host for sandal followed by D. repens, while C. junghuhniana suppressed the growth of sandal in field. It is therefore concluded that P. dulce can meet the primary host requirement for sandal in nursery and also used for successful sandal establishment in waste lands.